Formulation Development and Evaluation of Aripiprazole-IR Tablets By Using Different Starch Derivative Disintegrants. - Sireesha, P.; Mahammed, N. Lal; Reddy, K.Narendra Kumar (Asian Journal of Pharmaceutical Research and Development, 2014)
Aripiprazole used as anti-psychotic drug therapy in the form of immediate release tablet. This paper represents the disintegrants like starch, pre-gelatinated starch and corn starch which were used as suitable disintegrants for drug release. The investigation of drug release profile in the formulation of immediate release tablet with manufacturing includes the use of wet granulation processes. In this work the Characteristic study of drug release from immediate release tablets by taking 8 different formulations. It was obtained that disintegrants like starch, pre-gelatinated starch and corn starch formulations were shown comparable results with innovator.There was no more significant impact on physical properties of the formulations by interchanging starch, pre-gelatinated starch and corn starch. But higher percentage of drug release was observed when the formulation contained corn starh(f4) compared to other formulations. From this study it concluded that formulation(f4) which contained corn starch as disintegrant showed similar dissolution profile with innovator.